Understanding The History Of The National Movement Through The National Resurrection Museum In Building National Character - Siti Annisa (JURNAL HISTORICA, 2023)
The purpose of this research is to find out to what extent the National Awakening Museum can be an effective learning tool in learning history for visitors in understanding the history of the national movement and the formation of national character. The type of research used is descriptive research using the literature study method. Information can be obtained by using data collection techniques. Information is obtained from various literature using several scientific journals and other internet sources as references. The results of the study show that the National Awakening Museum can be an appropriate means of learning and innovation in studying history by making the National Awakening Museum an effective historical learning tool for visitors in understanding the history of the national movement and the formation of national character. Keywords: History of the National Movement, National Awakening Museum, History Education, National Character.